Salt Production Business Potential in Aceh as Capital for the Coastal Communities Welfare - Yety Rochwulaningsih (Journal of Maritime Studies and National Integration, 2018)
This article aims to identify and analyze small-scale salt production business potential in Aceh as one of the areas of salt production support in Indonesia. It is important to discuss in order to be a good and strategic capital to develop and improve Aceh coastal community welfare, of which the poverty rate is the second highest in Indonesia. By applying observation method, comprehensive interview, and focus group discussion, it can be determined that Aceh factually has the potential of marine and fishery resources including small-scale salt production business sector that can be used as a means to overcome the poverty of coastal communities because this sector provides employment for 45.59% productive age population. With quite high production area and small-scale salt production business potential and the number of entrepreneurs of 1,135 people in several regions like Aceh Besar, Pidie, Aceh Utama, East Aceh, etc., it is very rational if the small-scale salt production business becomes one of the gateways to overcome the poverty of coastal communities in Aceh. The development that can be performed is changing the entrepreneurs’ mindset to be the entrepreneur that can develop group business or cooperative by the supports of coaching, advocacy, and technology facilities as well as business capital.